PENGARUH VARIASI WAKTU PEMERAMAN TELUR ASIN DENGAN PENAMBAHAN ABU SABUT KELAPA TERHADAP KANDUNGAN KADAR KLORIDA, KADAR PROTEIN DAN TINGKAT KESUKAAN KONSUMEN - Emil Salim; Husain Syam; Muhammad Wijaya (Universitas Negeri Makassar, 2017)
Salted eggs are eggs preserved by marinated. This research aims to determine the effect of variations ripened of salted egg with addition of coconut fiber ash on the chloride and protein content, and the level of hedonic. Variable of this research were the variations ripened time of 7, 14 and 21 days. The research design by using a completely randomized design (CRD) single factor. The Parameters of this research were the content of chloride and protein, and the level of hedonic. Data of the research were analyzed by using ANOVA variance analysis techniques to further test DMRT (Duncan Multiple range test). The results of this research showed that the best chloride content and level of hedonic ripened in 21 days treatment, while for the best protein content ripened in 7 days treatment.